2014
DOI: 10.1002/jssc.201400193
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and complete separation of major cyclolinopeptides in flaxseed oil by reversed‐phase chromatography

Abstract: Organoleptic properties of flaxseed oil deteriorate during storage due to methionine oxidation in its major cyclolinopeptides. Cyclolinopeptide E was previously identified as being responsible for the manifestation of bitter taste with flaxseed oil ageing. We developed a chromatographic procedure to monitor the oxidation of major cyclic peptides in flaxseed oil. We also used liquid chromatography with mass spectrometry and high-efficiency core-shell reversed-phase sorbents to study the separation of cyclolinop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…The taste may also derive from the presence of oxidized forms of cyclolinopeptides that occur naturally in flaxseeds. The amount and type of these compounds in oil depends on flax variety, quality of seeds, methods of extraction and purification of the oil, and its storage time 28,29 .…”
Section: Organoleptic Characteristics Of Fresh Axseed Oilsmentioning
confidence: 99%
“…The taste may also derive from the presence of oxidized forms of cyclolinopeptides that occur naturally in flaxseeds. The amount and type of these compounds in oil depends on flax variety, quality of seeds, methods of extraction and purification of the oil, and its storage time 28,29 .…”
Section: Organoleptic Characteristics Of Fresh Axseed Oilsmentioning
confidence: 99%
“…However, the length of their HPLC gradient was 45 min. Lao et al [10] demonstrated the separation of 1 and 7 using a Kinetex TM Phenyl-Hexyl column with an HPLC run time of at least 25 min (actual run time is not stated). The novelty of our latest HLPC method developed is in its ability to resolve nine naturally occurring flax orbitides (CLs 2, 3, 5, 6, 8, 10, 13, 14, and 17) in 2.5 min.…”
Section: Faster Hplc Monitoring Offlinementioning
confidence: 99%
“…1). To date, twenty CLs, each possessing eight or nine amino acid residues, have been reported [2][3][4][5][6][7][8][9][10]. The biological activity of some CLs and their analogs is summarized in a recent review [11].…”
Section: Introductionmentioning
confidence: 99%
“…CL usually consist of eight or nine amino acid residues with molecular weight 960-1100 Da (Fig. 5) [97,99]. The nonoxidized CL are divided into three groups based on their number of methionine residues: 0 (e.g., CL1 and CL20), 1 (e.g., CL2, CL5, CL7 and CL18), or 2 (e.g., CL10 and CL14).…”
Section: Cyclolinopeptides Varieties and Structures Of CLmentioning
confidence: 99%
“…6). Traditionally, CL1 is usually considered the most stable CL due to its lack of methionine residues in its primary structure; moreover, other CL that containing methionines may produce more oxidized forms depending on the extent of oxidation [99,100].…”
Section: Cyclolinopeptides Varieties and Structures Of CLmentioning
confidence: 99%